Well-being Approach of the Power Systems Integrated to the Central Receiver Power Plants - Amir Ghaedi; Reza Sedaghati; Mehrdad Mahmoudian (AUT Journal of Electrical Engineering, 2023)
The solar power tower (central receiver power plant) as one type of concentrated solar thermal power systems can be used to generate electricity in a way similar to the thermal power plants and so, numerous large-scale central receiver power plants have been constructed and connected to the bulk power system to transfer their generated power to the power network. The variation in solar radiation leads the generated power of these power plants to change, too. Thus, the integration of these large-scale solar power towers into the power system results in some challenges that must be addressed. To study the effect of solar power towers on the power system, new techniques must be developed to consider the uncertain nature of these plants. For this purpose, in this paper, to investigate the impact of central receiver power plants on the operation studies of the power system, the well-being approach is proposed. To consider the solar power towers in the operation studies of the power system, a multi-state model is developed for these plants that both variations in the generated power and failure of composed components are taken into account. To evaluate the effectiveness of the proposed technique, the well-being models of two reliability test systems including RBTS and IEEE-RTS are determined and the effect of the central receiver power plant on the operation indices such as health state probability, risk, spinning reserve, peak load carrying capability and increase in peak load carrying capability is investigated.